2020
DOI: 10.20885/jaai.vol24.iss1.art6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organizational commitment and Cost management knowledge on the relationship between budget participation and managerial performance

Abstract: The purpose of this study is to examine the effect of organizational commitment and cost management knowledge on the relationship between budget participation and managerial performance. The data used in this study collected by distributed questionnaires to 700 managers work in manufacturing companies in Indonesia. The sample used in this study consists of 98 managers who involve in budgetary participation. Data were analyzed by using the Structural Equation Model (SEM) based Partial Least Square (PLS) with Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
0
1
1
1
Order By: Relevance
“…This research is in line with previous research conducted by [7] shows that organizational commitment does not succeed in moderating the effect of budget participation on managerial performance. However, it is not in line with research conducted by Gunawan&Santioso (2015) in [13]The results showed that organizational commitment moderates the effect of budgetary participation on managerial performance. The results of the third hypothesis indicate that the motivation variable does not moderate the effect of budget participation on managerial performance.…”
Section: Closing Conclusioncontrasting
confidence: 80%
“…This research is in line with previous research conducted by [7] shows that organizational commitment does not succeed in moderating the effect of budget participation on managerial performance. However, it is not in line with research conducted by Gunawan&Santioso (2015) in [13]The results showed that organizational commitment moderates the effect of budgetary participation on managerial performance. The results of the third hypothesis indicate that the motivation variable does not moderate the effect of budget participation on managerial performance.…”
Section: Closing Conclusioncontrasting
confidence: 80%
“…Budget participation supports management functions such as planning, implementation, and controlling on target. Based on these statements, it can be said that the budget participation process that improves budget quality can affect managerial performance as measured by its achievement of management functions were the key factors of management functions implemented and its success is through the budget [16]. There are four objectives of budget participation according to [17], namely as follows: 1.…”
Section: Research Methods 21 Budget Participation Budget Participatio...mentioning
confidence: 99%
“…Ermawati, 2017;Y. Ermawati et al, 2023;Febria et al, 2021;Fifi Suprida et al, 2022;Giusti et al, 2018;Heski, 2017;Isgiyarta et al, 2019;Kiswoyo et al, 2020;Maulida et al, 2021;Meirina & Aziora, 2020;Murdayanti et al, 2020;Novlina et al, 2020;Oyewo & Adyeye, 2018;Puji Handayati & Brilian Prastiti Andri Safitri, 2020;Putri, 2016;Rini et al, 2022;Setiawan & Rohani, 2019;Soedarman et al, 2023;Suryani & Pujiono, 2020;Widyawati, 2018;Wiratno et al, 2016;Wiwaha & Suryathi, 2018;Yunita Christy et al, 2021). Hasil penelitian ini menolak kesimpulan yang diberikan dari penelitian Ermawati & Apriyanti (2016); Oba et al, (2021) yang menunjukkan bahwa partisipatif anggaran tidak berpengaruh terhadap kinerja manajerial.…”
Section: Metodeunclassified